Di Balik Fleksibilitas: Eksplorasi Kepuasan dan Loyalitas Mahasiswa Pekerja di Universitas Ngurah Rai - Ni Putu Ayu Kristina Saraswati; I Gusti Ngurah Yoga Pebrinata; Octavianus Sumardana Pratama (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The transformation of higher education in the digital era has shifted learning paradigms toward more flexible, adaptive, and work-integrated systems. This shift is evident in the growing number of working students, including those at Ngurah Rai University, who simultaneously navigate academic and professional responsibilities. However, the flexibility offered by institutions does not always align with the quality of learning experiences perceived by students, creating significant challenges in fostering student satisfaction and loyalty. This study aims to critically explore the relationship between satisfaction and loyalty among working students at Ngurah Rai University within the context of flexible higher education, while identifying key strategic factors influencing both constructs.This research adopts a qualitative approach using a systematic literature review (SLR) method, analyzing recent national and international scholarly publications over the past five years (2020–2025). Data were analyzed through thematic analysis to identify patterns, relationships, and research gaps relevant to the characteristics of working students. The findings reveal that working student satisfaction at Ngurah Rai University is a multidimensional construct influenced by learning flexibility, the quality of academic and administrative services, curriculum relevance to labor market demands, and the quality of academic interaction. Learning flexibility emerges as a dominant factor; however, its effectiveness depends on interactive pedagogical design and meaningful student engagement. Furthermore, satisfaction significantly influences student loyalty, which is reflected in long-term commitment, emotional attachment, and positive word-of-mouth intentions. Nevertheless, this relationship is dynamic and mediated by perceived value and overall learning experience. The study also identifies a gap between the implementation of flexible learning systems and the actual needs of working students. Therefore, Ngurah Rai University is required to undertake not only structural but also pedagogical transformation through the adoption of more adaptive, contextual, and experience-based student-centered learningapproaches. This study contributes theoretically to higher education management literature and offers practical implications for institutions in designing sustainable strategies to enhance working student satisfaction and loyalty.